Policy and choice public finance through the lens of behavioral economics - Congdon, William J.; Kling, Jeffrey R.; Mullainathan, Sendhil (Washington, D.C. Brookings Institution Press, 2011)
"Applies the psychological insights of behavioral economics to economic concepts such as moral hazard, deadweight loss, and incidence. Explores how deviations from the standard economic model of decisionmaking--imperfect optimization, bounded self-control, and nonstandard preferences--might affect public finance policy regarding externalities, information asymmetries, poverty, and taxes"--Provided by publisher.
The promise -- Psychology and the foundations of public finance -- Psychology and economics -- Behavioral economics and public finance -- Behavioral economics and public finance in practice -- Asymmetric information -- Externalities and public goods -- Poverty and inequality -- Taxation and revenue.
Includes bibliographical references and index.
Keywords: Finance, Public -- Psychological aspects; Economics -- Psychological aspects; Finance, Public -- Decision making; Human behavior -- Economic aspects